Upaya Guru dalam Meningkatkan Minat Baca Siswa Di SDN 4 Kopang - Rizki, Pebrianti Milenia; Kemala Dewi, Nurul; Husniati, Husniati (Mataram University, 2025)
This study aims to examine the efforts made by teachers to improve students’ reading interest at SDN 4 Kopang. This research employed a descriptive qualitative approach. The subjects of the study were upper-grade teachers at SDN 4 Kopang. Data were collected through observation, interviews, and documentation. The data analysis techniques included data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation. The results of the study indicate that the efforts made by teachers at SDN 4 Kopang to improve students’ reading interest include preparing reading corners, implementing a 15-minute reading program before lessons begin, providing reading materials, giving motivation, and offering rewards. The factors influencing students’ reading interest at SDN 4 Kopang are divided into internal and external factors. Internal factors include students’ limited reading ability and the lack of reading habits, while external factors consist of environmental factors and school-related factors.